DIAGNOSIS AND MANAGEMENT MOLECULER DETECTION OF BLOODSTREAM INFECTION - Evriarti, Paulina Rosa; Wani Devita Gunardi (Universitas Islam Negeri Alauddin Makassar, 2024)
Examination for diagnosing sepsis or blood infections is conducted through blood culturing but this methode has several drawbacks such as a rather long incubation time. Therefore, the author has compiled this literature review to delve deeper into the potential and challenges of molecular diagnosis for blood infections or sepsis based on previous research findings. This Literature Review method was conducted using electronic databases including several databases such as Google Scholar, PubMed, and Semantic Schoolar. Base on the research, author get 8 journal that were discuccion in this journal. Molecular detection has potential function tn the future but research on the limitations of the method and optimization of PCR methods for detecting pathogens in the blood needs further investigation.